Association between changes in sleep duration and the risk of incident depressive symptoms among Chinese middle-aged and older adults - LiHan Lin; YiLing Dai; Jiajun Huang; Wei Zheng; Yiping Liu (PLoS ONE, 2025)
Background Although insufficient sleep is a known risk factor for depressive symptoms among middle-aged and older adults, prior studies have mostly focused on baseline sleep duration. This study investigates the association between changes in sleep duration and the risk of incident depressive symptoms in this population. Methods This study utilized data from the China Health and Retirement Longitudinal Survey (CHARLS), covering waves from 2011 to 2018. Sleep duration was assessed through self-report and categorized as short (<6 h/day), normal (6–8 h/day), and long (> 8 h/day). Changes in sleep duration were determined based on measurements at baseline and the 2-year follow-up. Depressive symptoms were evaluated using the 10-item Center for Epidemiological Studies Depression Scale (CESD-10). Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazards models after adjusting for potential confounders, and sensitivity analyses were conducted to assess the robustness of the associations by applying alternative cut-off values for sleep duration classification and by conducting stratified subgroup analyses. Results A total of 5,636 participants (female: 44.7%, mean age: 58.1 ± 8.8 years) were included. During a median follow-up of 4.14 years, 1,656 participants developed depressive symptoms. Short sleep at baseline was associated with a higher risk of depressive symptoms (HR = 1.33, 95% CI: 1.22–1.45). A change from normal to short sleep further increased the risk (HR = 1.48, 95% CI: 1.24–1.76), suggesting a greater hazard than baseline short sleep alone. A change from long to short sleep also elevated the risk (HR = 1.49, 95% CI: 1.16–1.91). These associations remained robust in sensitivity analyses. Conclusion Among Chinese adults aged 45 years and older, maintaining a normal sleep duration and avoiding a shift to short sleep may help prevent the onset of depression. Individuals who experience a marked decline in sleep duration should be considered a key target population for the prevention of depressive symptoms.